The Transformation of Islamic Education in Malabar: From Othupalli to Primary Madrasa - KP, Hassan Shareef (Journal of Islamic Educational Research, 2025)
This study investigates the transformation of primary Islamic education in Malabar, focusing on the evolution from the informal Othupalli system to the structured Primary Madrasa system during the twentieth century. This transformation was driven by socio-cultural shifts, political influences during colonial and postcolonial periods, and active community participation, which collectively ensured the preservation and modernization of Islamic education amid the rise of secular schooling. The continued use of Arabi-Malayalam highlights cultural adaptability in sustaining religious knowledge transmission. This study contributes a historically grounded, localized perspective to global scholarship on Islamic educational reform, emphasizing the interplay of linguistic innovation, community agency, and institutional modernization. It underscores the resilience of Malabar’s Muslim community in negotiating educational preservation and reform. The findings call for ongoing reforms that integrate holistic Islamic values with contemporary pedagogical approaches to address current challenges and ensure the madrasa system’s future relevance.